Ecological Form System and Aesthetics in the Age of Empire - Hensley, Nathan; Steer, Philip (Fordham University Press, 2019)
Hensley and Steer look to join the conceptual tools of contemporary ecocriticism with the rich archive of nineteenth century thinking about imperial and ecological intertwinement. This collection of essays draws on that archive to demonstrate the relevance of Victorian thought for current theory and practice. Ecological Form argues that ecology, the empire, and literary thinking were inseparable during the Victorian period; and its claim that connections among these domains challenge the methodological assumptions of both contemporary ecocriticism and literary and cultural studies